IMPLEMENTASI TOTAL QUALITY MANAJEMEN DI SMP MUHAMMADIYAH I DEPOK SLEMAN - Nur Hamidi (Al-Misbah (Jurnal Islamic Studies), 2018)
Entering the past decade, the issue of quality has always been the talk of the actual, especially in the context of education management. Recognized or not, the quality of Islamic education institutions are still largely under the quality of education in general. Various attempts have been made and many of the concepts that have been applied, but everything seemed not bring significant improvement. "Total Quality Management (TQM) or Integrated Quality Management (MMT) as an effort to improve the quality of education in Islamic educational institutions. Although at first the concept of MMT is only known in the industry, but the amazing success invite the interest of education experts, 3 to study it more deeply, formulate operational patterns of adoption, and to create a model in teknical to apply. This research was conducted in SMP Muhammadiyah I Depok Sleman Yogyakarta. Consideration is SMP Muhammadiyah I Gurgaon is one of the Islamic educational institutions (schools distinctively Islamic) 5 formal mission has always been to apply concepts of Quality Management (TQM). This study resulted in that SMP Muhammadiyah I Depok already implementing Total Quality Management in the management of education. However, the application of Total Quality Management in SMP Muhammadiyah I Depok can be said is not fully maximized, in the sense that there are still some things that need to be evaluated together.